Identification of Metabolite Compounds from A Ethanol Extract of Caulerpa racemosa using LC-MS/MS with Inhibitory Activity of Interleukin-1β and Expression Inhibitory Nitric Oxide Synthase Enzyme; In Silico Virtual Screening - Prayogo, Ega Widya; Sholikhah, Irawati; Suciati, Suciati; Ekasari, Wiwied; Widyowati, Retno (Trends in Sciences, 2024)
Osteoarthritis (OA) is the prevailing kind of arthritis, impacting a substantial number of individuals globally. The incidence of OA is on the rise and is projected to further increase due to the aging population and escalating rates of obesity. This study aims to evaluate the anti-OA potential of Caulerpa racemosa. The Caulerpa racemosa 96 % ethanol extract of the plant was analysed using LC-MS/MS. The metabolite compositions were identified as polyunsaturated fatty acids, terpenes, bisindole alkaloids and diterpenoids. The 18 compounds analysed by LC-MS/MS, and the binding affinity of the compounds to the target proteins Interleukin-1 (PDB ID: 1ITB) was assessed by molecular docking fucosterol (∆G = –8.29 kcal/mol), variolin A (∆G = –8.02 kcal/mol), and clionasterol (∆G = –7.50 kcal/mol) and Nitric Oxide Synthase Inducible (3E7G) was assessed by molecular docking. Brassicasterol (∆G = –9.25 kcal/mol), fucosterol (∆G = –9.20 kcal/mol) and 24-methylenecholesterol (∆G = –9.04 kcal/mol) exhibited the highest docking scores, indicating their strong potential as inhibitors of IL1β and nitric oxide (NO). This knowledge is valuable for the future bioassay investigations about the possible applicability of these medicines as innovative solutions for OA. HIGHLIGHTS The ethanol extract of Caulerpa racemosa, with a concentration of 96 %, comprises polyunsaturated fatty acids, terpenes, bisindole alkaloids and diterpenoids. Analysis utilizing liquid chromatography-tandem mass spectrometry (LC-MS/MS) identified a total of 18 chemicals. The efficiency of 5 phytoconstituents (fucosterol, variolin A, clionasterol, brassicasterol and 24-methylenecholesterol) in silico antiosteoarthritis was evaluated. Fucosterol exhibited the highest negative average value of energy affinity, indicating stronger binding affinities for inhibiting IL-1β and the Inhibitory Nitric Oxide Synthase Enzyme compared to the other components studied. GRAPHICAL ABSTRACT